Kajian Literatur: Intervensi Religius Islam dan Dampaknya pada Pasien Stroke - Suciari Tri Utami; Fitria Handayani (Holistic Nursing and Health Science, 2021)
Introduction: Stroke becomes the main factor of longterm disability. Changes in physical condition increase the risk of psychological disorders. Indonesian citizen has Islam religion mostly. The study of Islamic religious intervention was few. Religious interventions had been conducted however no review described the Islamic religious interventions and the impacts. This study aimed to describe the intervention of Islamic religious and its impacts among stroke patients. Methods: The research method used scoping review using databases such as Sciendirect, CINAHL, Medline, Taylor & Francis, JSTOR, PubMed, and search engine Google Advance. The criteria for the articles reviewed were articles in English or Indonesian with the SINTA index 1-2, articles published on 2010-2020, articles accessed in full text, method was quasi experiment or randomized control trial, articles were original research. The key words were Islamic spiritual or religious and stroke. Search results obtained five articles that required the inclusion criteria. Results: Review found that memorizing of Al Qur’an, listening Al Qur’an, motivation and prayer, salah prayer and Quranic teaching. Impacts of Islamic spiritual and religious intervention have positive impact in patient’s physiological and psychological such as increased functional communication, independence, improvement of neurological clinical outcome, motoric function, balance, motivation, quality of life, and decreased the anxiety and depression. Conclusion: Islamic spiritual or religious intervention in stroke survivor was the part nursing care that promising improved clinical outcome.